The Roles of Awareness, Interest, Evaluation, Trial on Adoption and its Impact on Purchase Decision: Study on New Product of ”Wuling” Electric Car Consumers in Bandung - Cahyati, Tetet; Munandar, Dadang (Jurnal Soshum Insentif, 2023)
The objectives of this study is to know the influence of the new product adoption on purchase decision among the consumers of the Wuling Electrical Vehicle in Bandung. The research employs a quantitative approach and survey. By using the purposive method, 96 consumers in Bandung were selected as the respondents of the study. The writer uses path analysis to analyze the data. Findings of the research are as follows: 1) Awareness, Interest, Evaluation and Trial affect significantly Adoption simultaneously; 2) Awareness affects significantly Adoption partially; 3) Interest affects significantly Adoption partially; 4) Evaluation affects significantly Adoption partially; 5) Trial affects significantly Adoption partially; and 6) Adoption affects Purchase Decision significantly. Thus, the adoption process of the new electric car positively affect the consumers purchase decisions whether or not they will buy the electrical vehicle.